Engineering Escherichia coli for targeted biosynthesis of neohesperidin as an adjuvant therapeutic strategy for colorectal cancer - Annabella Dai (Journal of Food Science, Nutrition and Health, 2026)
Colorectal cancer (CRC) is the third most prevalent cancer and the second most deadly cancer in the world, and current treatments have significant side effects and drug resistance. Citrus plants contain flavonoids glycosides, such as neohesperidin, which has antioxidant, anti-inflammatory, immunomodulatory and antitumor properties, making it a promising CRC adjuvant. However, conventional extraction is limited by low natural abundance, poor consistency and low bioavailability. In this study, E. coli BL21(DE3) were engineered to produce neohesperidin de novo from naringenin by two integrated modules that convert naringenin to hesperetin and then to neohesperidin. The neohesperidin yield reached 4.55 mg/L using naringenin as the substrate. These findings provide a precision, scalable platform for adjuvant CRC therapy.